Green supply chain management and SMEs environmental performance: green HRM practices as antecedent from service sector of emerging economy - Aldaas, Raghad; Mohamed, Rosmah; Ali, Mass Hareeza; Ismail, Noor Azlin (Emerald Group Publishing, 2022)
Purpose: The research aimed to study the influence of green human resources management practices (GHRMPs) on green supply chain management (GSCM) and environmental performance while examining how those green practices affect environmental performance. Design/methodology/approach: The study investigated 314 cases (responses) from the small and medium-sized enterprises belonging to the service sector from an emergent economy (i.e. Oman). The study model was developed based on the theory of resource-based view and the theory of ability, motivation and opportunity. The structural equation modeling was used for hypotheses testing using SmartPLS 3 software. Findings: Based on the findings, green hiring and green training and innovation have a positive and significant effect on GSCM, while both of them have no effect on environmental performance. Further, green performance management and compensation positively influenced the environmental performance but not GSCM. Furthermore, GSCM significantly and positively influenced environmental performance. Originality/value: GHRMPs and GSCM can enhance environmental performance. Organizations should consider this interesting finding if they aim to reduce their negative environmental effect, conserve energy, prevent pollution and recycle garbage. Despite the fact that the present environment-friendly culture is still in its infancy, it adds uniqueness to this research by investigating the phenomenon's importance.